DSM-5 substance use disorders among college-age young adults in the United States: Prevalence, remission and treatment. Issue 6 (17th August 2020) - Arterberry, Brooke J.; Boyd, Carol J.; West, Brady T.; Schepis, Ty S.; McCabe, Sean Esteban
Abstract: Objective: To determine the prevalence, remission, and treatment associated with DSM-5 substance use disorders (SUDs) among young adults based on college attendance. Participants: The population-based sample included 2, 057 young adults aged 19–23 in college/school and 1, 213 not currently attending college/school who participated from April 2012 through June 2013. Methods: Face-to-face interviews were conducted as part of a cross-sectional national survey. Results: The prevalence of any past-year DSM-5 SUD was 39.6% among young adults in college and 44.5% among those not attending college. Past-year tobacco use disorder and multiple DSM-5 SUDs were more prevalent among those not attending college. Among those with prior-to-past-year SUDs, abstinent remission was low among college (1.0%) and noncollege (1.9%) young adults. Conclusions: Approximately two in five U.S. college students had at least one past-year DSM-5 SUD. Sustained abstinent remission from SUDs is extremely rare (1–2%) and the majority of those with SUDs do not receive treatment.